Military Health Strategies Against Narcotics Threats within the CBRNE Framework - Harefa, Faonaso; Yahdiana Harahap; Dian Andriani Ratna Dewi; Nurrobi, R.M. Tjahya; Sutanto (Khazanah Sosial, 2026)
This study positions narcotics as an emerging non-traditional threat within the CBRNE framework due to its chemical nature and its impact on public health and national resilience. Drug abuse in Indonesia has evolved into a multidimensional threat that not only disrupts social stability but also weakens public health resilience. This study aims to analyze the role of military health within its service and health support functions based on existing regulations, particularly its contribution to combating drug threats as a form of non-military threat endangering young generations and national defense. Using a descriptive qualitative method with data analysis conducted through NVivo 12. The findings reveal that regulation based military health support has a positive impact in reducing drug abuse and trafficking while strengthening both public health resilience and national defense. However, the involvement of military health in cross sectoral collaboration remains limited, despite its proven capability and resilience in managing health crises, as demonstrated during the Covid-19 pandemic.: This study emphasizes the need to strengthen the role of military health in drug control through formal cooperation mechanisms, such as a Memorandum of Understanding (MoU) with the leading sectors Badan Narkotika Nasional, the Kepolisian Negra Republik Indonesia, and Kementerian Kesehatan to ensure clear synergy, avoid overlapping authority, and establish an integrated and sustainable national health defense system. However, the study identifies a gap in formal institutional integration, which limits the optimization of military health roles